1995
DOI: 10.1016/0029-7844(95)00109-5
|View full text |Cite
|
Sign up to set email alerts
|

Cervical carcinoma: Computed tomography and magnetic resonance imaging for preoperative staging

Abstract: Compared with CT, MRI offered significantly improved evaluation of tumor size, stromal invasion, and local and regional extent of disease in pre-treatment imaging for cervical cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
152
1
17

Year Published

1997
1997
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 351 publications
(179 citation statements)
references
References 20 publications
9
152
1
17
Order By: Relevance
“…CT can detect lymph nodes that are enlarged by more than 1 cm but cannot determine lymph node architecture. 40 Subak et al 35 reviewed studies comparing the accuracy of CT and MRI in the preoperative evaluation of parametrial invasion, disease stage, and lymph node involvement. Yang et al 36 compared helical CT and dynamic MRI, evaluating their sensitivity (64.7% vs. 70.6%), specificity (96.6% vs. 89.9%), positive predictive value (84.6% vs. 66.7%), negative predictive value (90.5% vs. 91.4%), and accuracy (89.5% vs. 85.5%).…”
Section: Computed Tomographymentioning
confidence: 99%
See 2 more Smart Citations
“…CT can detect lymph nodes that are enlarged by more than 1 cm but cannot determine lymph node architecture. 40 Subak et al 35 reviewed studies comparing the accuracy of CT and MRI in the preoperative evaluation of parametrial invasion, disease stage, and lymph node involvement. Yang et al 36 compared helical CT and dynamic MRI, evaluating their sensitivity (64.7% vs. 70.6%), specificity (96.6% vs. 89.9%), positive predictive value (84.6% vs. 66.7%), negative predictive value (90.5% vs. 91.4%), and accuracy (89.5% vs. 85.5%).…”
Section: Computed Tomographymentioning
confidence: 99%
“…49 The absence of parametrial invasion holds great importance in determining whether a patient is a surgical candidate. The reported negative predictive value of MRI in detecting parametrial invasion is approximately 95% 35 ; when the fibrocervical stroma surrounding the tumor is seen as intact on imaging, the possibility of parametrial spread can be readily excluded. In contrast, the positive predictive value for parametrial invasion is considerably lower, because imaging cannot easily distinguish the occurrence of peritumoral reactive changes from the presence of invasive tumor.…”
Section: Mrimentioning
confidence: 99%
See 1 more Smart Citation
“…Russell et al, in 1992, reported for the first time on the value of pelvic MRI in designing the lateral fields of the box technique [5] . MRI offers the possibility of visualising the anatomy of the pelvis on all planes and enables much better evaluation of soft tissue structures and tumour depiction than CT [11][12][13][14][15][16] . Russell [3,6,7] .…”
Section: Figurementioning
confidence: 99%
“…Also critical is the assessment of prognostic variables such as the depth and width of stromal invasion, local extension into the vagina or the parametrium, as well as the spread of the tumour into the pelvic wall and beyond into the bladder and/or the rectum [1,2,13,15]. In the assessment of primary cervical cancers, the value of MRI is well documented [4,5,16,17]. More recently, increasing amounts of data also have shown that 18 FDG PET may detect an intense metabolic signal at the level of the primary site with a high sensitivity (81-100%) [10,11,12,13,14,18,19,20].…”
Section: T Stagingmentioning
confidence: 99%